KOMPETENSI PROFESIONALISME GURU - Helmi, Jon (AL-ISHLAH: Jurnal Pendidikan, 2015)
A professional teacher should master the four competencies , namely 1. Pedagogic competence is the ability of teachers to manage the learning of students . 2. Professional Competence . Namely the ability of teachers to keep abreast of  the latest science for the development of science is always dynamic . 3. Social competence it will be  be seen whether a teacher can work together with the community and the students and other teachers . 4. Competence Personality . These competencies associated with the personality of the teacher . teachers  should possess noble trait that can be a model for his students.